Phase noise tolerant inter-carrier-interference cancellation for WDM superchannels with sub-Nyquist channel spacing - Yao, Shuchang (2013)
We propose and demonstrate a novel multi-input multi-output (MIMO) equalization based inter-carrier-interference (ICI) cancellation approach employing constant modulus algorithm (CMA) for supperchanels with sub-Nyquist channel spacing, where optical combs are used as optical sources. Compared with the least mean square (LMS) algorithm based ICI canceller, the proposed approach has comparable capability to accomplish the ICI mitigation for 56 Gbaud dual-polarization quadrature phase shift keying (DP-QPSK) signals with tight channel spacing till 50 GHz. In particular, compared with the LMS-MIMO based ICI canceller, the optical linewidth tolerance of 6 MHz is relaxed to 20 MHz given a 1dB required optical signal-to-noise ratio (OSNR) penalty for the CMA-MIMO based ICI canceller. Meanwhile, the CMA-MIMO based ICI canceller is ideal for real-time processing, since the number of parallel processing pipelines can be greater than 240 even in the presence of large linewidth.